Agroecological Fertilisation Practices to Improve Sustainability and Circularity in Maize Crop Systems - Martha Elena Domínguez-Hernández; Elisa Domínguez-Hernández; Arnulfo Domínguez-Hernández; María del Carmen Valderrama-Bravo; Rosalba Zepeda-Bautista (Biology and Life Sciences Forum, 2023)
Agroecological practices such as organic fertilisation offer a sustainable approach to crop systems. In this research, organic fertilisers made from a mixture of nejayote (lime water) and ovine manure were evaluated in maize. Several indexes and indicators were calculated based on field data. The results demonstrated that nejayote-manure fertilisers improve soil quality (SQI = 14.1), enhance efficiency in nutrient utilisation (increased yield, IY = 4.2 Mg ha−1), and promote greater production biomass compared to chemical fertilisation. Organic fertilisation reduced dependency on external inputs and non-renewable energy, increased sustainability in maize, and facilitated the closure of nutrient cycles by integrating livestock, crop, and agro-industrial systems.